Tata Kelola Pemerintahan Dalam Implementasi Kebijakan Ekonomi Hijau Untuk Mewujudkan Kemandirian Masyarakat Pesisir Karangantu Kabupaten Serang - Ita Rosita Wahyiah; Diah Ayu Pratiwi; Eli Apud Saepudin (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Developing a green economy in coastal areas requires governance capable of integrating environmental sustainability with enhanced community economic self-reliance. This study aims to analyze the governance of green economy development—leveraging fishery potential—to foster the self-reliance of the coastal community in Karangantu. A qualitative approach utilizing a case study method was employed. Data were gathered through in-depth interviews with ten informants—comprising local government officials, coastal community members, fishery business operators, and relevant stakeholders—and supplemented by observation and documentation. Data analysis involved reduction, presentation, and conclusion drawing. The results indicate that while the governance of green economy development in Karangantu is supported by government roles in facilitation, guidance, and service access, implementation remains not fully integrated. Key findings reveal that inter-actor collaboration lacks consistency and that limited community capacity remains a constraint on increasing the value-added of fishery products. Conversely, developing businesses based on local potential and improving market access present strategic opportunities to strengthen community economic self-reliance. The study contributes an integrative governance model linking government roles, inter-actor collaboration, the green economy, and coastal community capacity building.